2019
DOI: 10.5194/acp-2019-135
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Summertime aerosol volatility measurements in Beijing, China

Abstract: <p><strong>Abstract.</strong> Volatility plays a key role in affecting mass concentrations and lifetime of aerosol particles in the atmosphere, yet our knowledge of aerosol volatility in relatively polluted environment, e.g., north China remains poor. Here aerosol volatility in Beijing in summer 2017 and 2018 was measured using a thermodenuder (TD) coupled with an Aerodyne high-resolution aerosol mass spectrometer (AMS) and a soot particle AMS. Our results showed overa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
25
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 51 publications
8
25
2
Order By: Relevance
“…In particular, whether SOA materials condensed on BC particles have similar chemical characteristics to those externally mixed with BC particles 10 remains poorly understood. Previous observations in urban environments have reported that the mass spectral features of ambient OOA components identified by the PMF analysis were significantly different between the two co-located measurements even though their temporal variabilities strongly correlated to each other (Chen et al, 2018;Lee et al, 2017;Liu et al, 2019;Massoli et al, 2015;Wang et al, 2020;Xu et al, 2019;Zhao et al, 2019). Given our observations that vaporization scheme plays a critical role in the fragmentation process of oxygenated organic species,…”
Section: Insight Into Ambient Ooa Characteristicssupporting
confidence: 63%
See 1 more Smart Citation
“…In particular, whether SOA materials condensed on BC particles have similar chemical characteristics to those externally mixed with BC particles 10 remains poorly understood. Previous observations in urban environments have reported that the mass spectral features of ambient OOA components identified by the PMF analysis were significantly different between the two co-located measurements even though their temporal variabilities strongly correlated to each other (Chen et al, 2018;Lee et al, 2017;Liu et al, 2019;Massoli et al, 2015;Wang et al, 2020;Xu et al, 2019;Zhao et al, 2019). Given our observations that vaporization scheme plays a critical role in the fragmentation process of oxygenated organic species,…”
Section: Insight Into Ambient Ooa Characteristicssupporting
confidence: 63%
“…Figure 3a compares the ambient OOA components determined by the TV and LV schemes (i.e., concurrent HR-ToF-AMS and SP-AMS LV scheme measurements) at the same location if their time series of mass concentrations are strongly correlated (i.e., R > 0.75). Table S1 summaries the characteristics of the OOA components observed in Beijing summer (Xie et al, 2019a;Xu et al, 2019), Beijing winter (Wang et al, 2019;Xie et al, 2019b),…”
Section: Changes In # / # Ratiomentioning
confidence: 99%
“…At the time of the SARS outbreak, there were no specialized health emergency agencies, established plans, systems, mechanisms, or applicable legal framework. Faced with severe challenges, the Chinese government responded by developing a health emergency system based on a "one plan, three systems" strategy, and continued to strengthen basic health services [9]. "One plan" refers to the emergency plan, and "three systems" refers to establishing and improving (1) emergency response systems, (2) mechanisms, and (3) legal systems.…”
Section: Comprehensive Advancement Of China's Health Emergency Systemmentioning
confidence: 99%
“…According to the basic theory on transmission of elastic stress wave in continuous medium [18,19], the equations of particle motion are deduced and can be expressed as…”
Section: Relationship Between Velocities Of Seismic Waves and Dynamicmentioning
confidence: 99%